2018
DOI: 10.1002/anie.201807996
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes with Cobalt Corroles for Hydrogen and Oxygen Evolution in pH 0–14 Solutions

Abstract: Water splitting is promising to realize a hydrogen‐based society. The practical use of molecular water‐splitting catalysts relies on their integration onto electrode materials. We describe herein the immobilization of cobalt corroles on carbon nanotubes (CNTs) by four strategies and compare the performance of the resulting hybrids for H2 and O2 evolution. Co corroles can be covalently attached to CNTs with short conjugated linkers (the hybrid is denoted as H1) or with long alkane chains (H2), or can be grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
136
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 63 publications
(85 reference statements)
4
136
0
Order By: Relevance
“…Herein, we report a strategy by covalently grafting Co corrole 1 on conductive Fe 3 O 4 nanoarrays grown on Ti mesh ( 1 @Fe 3 O 4 NR/TM). Co corrole 1 is active and robust to catalyze OER and ORR . The 3D self‐supported Fe 3 O 4 NR/TM has advantages to offer large electrochemical surface area and to ensure rapid charge transfer and mass diffusion .…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we report a strategy by covalently grafting Co corrole 1 on conductive Fe 3 O 4 nanoarrays grown on Ti mesh ( 1 @Fe 3 O 4 NR/TM). Co corrole 1 is active and robust to catalyze OER and ORR . The 3D self‐supported Fe 3 O 4 NR/TM has advantages to offer large electrochemical surface area and to ensure rapid charge transfer and mass diffusion .…”
Section: Methodsmentioning
confidence: 99%
“…[151] It was revealed that the fluorobenzene might be away to improvethe electrophilicity of MÀO( Mi sm etal), which would contribute to nucleophilic attack by water.C hen and co-workersf urthers tudied OÀOb ond formation on CoH bF CX-CO 2 Ht hrough DFT calculations. [156] Direct amidation coupling has provedt ob eas imple way to immobilize Co-corroles on CNTs, and would be ap romising prospecti no ther electrocatalytic applications. In 2014, Cao and co-workers studied the OER performance of [Co(tpfc)(py) 2 ] (tpfc:5 ,10,15-tris(pentafluorophenyl)corrole), and found that this cobalt corrole catalystw as stable during the OER.…”
Section: Mononuclear Cobalt-based Catalystsmentioning
confidence: 99%
“…The resulting CNTse ngineered with Co corroles were used as electrocatalysts for the hydrogen evolutionr eaction (HER) and the oxygen evolution reaction (OER) in aqueous solutions of pH 0, 7, and 14. [39][40][41][42][43] Despite these progresses,h owever, convenient methods for covalenti mmobilization under mild conditions are still needed.Carbon nanotubes (CNTs) are broadly used as supports for electrochemical applications because of their large surface areas and good electrical conductivities. This is likely because the large surface area and good electricalc onductivity of CNTsc an be well preserved during the amidationr eactionu nder mild conditions.…”
mentioning
confidence: 99%
“…[1][2][3] During the last decade,avariety of molecular complexes based on earth-abundant transition-metal elements including Mn, [4][5][6][7] Fe, [8][9][10][11][12][13][14] Co, [15][16][17][18][19][20][21] Ni, [22][23][24][25][26][27][28] and Cu [29][30][31][32][33] have been identified as catalystsf or these two reactions. [39][40][41][42][43] Despite these progresses,h owever, convenient methods for covalenti mmobilization under mild conditions are still needed. [34][35][36][37][38] Covalent immobilizationi su seful to improvec atalyst stabilitya nd performance and benefitst he recycling of electrocatalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation